At the Controls : Questioning Video and Computer Games - Neil Anderson (Mankato, MN, United States Capstone Press, 2007)
"Sports games, fantasy games, war games - there are hundreds of video games out there. So how do companies get gamers to play theirs? And what are they really trying to say? Well, grab your controller. It's time to ask questions about video game messages."
Keywords: How We Organize Ourselves -- -Digital Media